Respiratory Symptoms and Lung Function in Poultry Confinement Workers in Western Canada - Shelley P Kirychuk; Ambikaipakan Senthilselvan; James A Dosman; Victor Juorio; John JR Feddes; Philip Willson; Henry Classen; Stephen J Reynolds; Wilhelm Guenter; Thomas S Hurst (Canadian Respiratory Journal)
OBJECTIVE: To determine whether poultry production methods impact respiratory health, and whether poultry farmers have more respiratory symptoms and lower lung function than comparison control groups.